The US geopolitical codes and its influences on the US-Iran Relations: The case of George W. Bush's presidency. - Naji, Saeid; Jawan, Jayum (Canadian Center of Science and Education (CCSE), 2011)
This paper attempts to explain the US-Iran political relations from the geopolitical perspective. It focuses on George W. Bush’s presidency as a remarkable period in two states’ relations. Concentrating on the US geopolitical codes, this work aims to study the political leaders’ beliefs and also the influences of these ideas on the states’ foreign policy. The research also stresses on some of the world’s geopolitical changes in the geopolitical world order context. With the end of Iran-Iraq war, inimical relation of the US-Iran was promoting, and it even entered a more critical phase with the occurrence of changes in the US foreign policy towards Iran, when Bush was elected as the US president in 2001 and especially after September 11th attacks. At this point, Iran was introduced as an “axis of evil” and this asseveration strengthened hostility between the two countries. With the election of Ahmadinejad as Iran’s president in 2005, Iran’s political behavior also underwent drastic changes. As a result, both countries, based on their leaders’ beliefs, pursued their policies in the regional and global level to access to different objectives, in line with the ideas that had been derived from their geopolitical-ideological assumptions.